The impacts of preferential college admissions for the disadvantaged: Experimental evidence from the PACE programme in Chile - Ryan Cooper; Javier Guevara; James Kinder; Mario A. Rivera; Antonia Sanhueza; Michela M. Tincani (Institute for Fiscal Studies (IFS), 2022)
Participation in university is highly unequal across socio-economic lines globally (UNESCO, 2017). This has led many governments and admission officers to introduce preferential college admissions for disadvantaged students. This report studies the impacts that preferential admissions can have on the higher-education admission, enrolment and retention of disadvantaged students. We answer these research questions in the context of a programme called PACE (Programa de Acompa\~namiento y Acceso Efectivo a la Educación Superior, Programme for the Support and Effective Access to Higher Education) in Chile. PACE targets disadvantaged high schools and guarantees admission to a selective university for students who graduate in the top 15% of their school, waiving the requirement to obtain a sufficiently high score on the standardised entrance exam. Similar programmes, known as percentage plans, have been used in other countries (e.g., California, Florida and Texas have state-wide percentage plans). Specifically, this report evaluates the impacts of the PACE programme on higher-education admissions and on higher-education enrolment of the disadvantaged students targeted by the programme, up to four years after the end of secondary education. To identify policy impacts, we exploit the randomized expansion of PACE that occurred in 2016. Our main findings are the following. [...]
Keywords: 330; Studium; Bildungschancen; Hochschulpolitik; Soziale Ungleichheit; Wirkungsanalyse; Chile